Reforming a School System, Reviving a City The Promise of Say Yes to Education in Syracuse - Maeroff, Gene I.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
a bold investment in education turn around the economy of an entire city? Gene I. Maeroff, former national education correspondent for the New York Times , explores how the nonprofit group Say Yes to Education has instituted a network of reforms in Syracuse, New York, that aim to expand the city's the middle class by supporting its children.
Keywords: Science; Science; Science, general